Contact fatigue in low-cycle loading of Wc-Co hard alloys for metal working - Fal'kovskii, V.A.; Kuralina, M.V.; Travushkin, G.G. (Проблемы прочности, 1985)
The proposed experimental method of examining the resistance to low-cycle fatigue makes it possible to approximate the laboratory conditions to the real loading conditions and predict the behavior of the alloy in service,